Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1179/joc.1996.8.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Fractional Maximal Effect Method: Comparative Interaction Studies of Ciprofloxacin and Protein Synthesis Inhibitors

Abstract: The performance of the recently developed Fractional Maximal Effect (FME) method was evaluated along with the conventional checkerboard technique and time-kill method. Ciprofloxacin in combination with tobramycin was tested against Escherichia coli and Pseudomonas aeruginosa and in combination with tetracycline, chloramphenicol, erythromycin against Escherichia coli. Two combinations, amoxicillin-tetracycline (antagonistic) and tobramycin-ticarcillin (synergistic), were included as reference interactions. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The FME method demonstrated a similar degree of antagonism against ciprofloxacin by tetracycline, chloramphenicol and erythromycin, and a much lower level of inhibition by tobramycin. 12 Data from our study and from the study by Li et al 12 indicate that the antagonism between quinolones and fusidic acid might not arise from constitutional properties.…”
Section: Ertek H Yazgi S Erol Et Al In Vitro Antagonism Between Fusidic Acid and Quinolonessupporting
confidence: 47%
See 1 more Smart Citation
“…The FME method demonstrated a similar degree of antagonism against ciprofloxacin by tetracycline, chloramphenicol and erythromycin, and a much lower level of inhibition by tobramycin. 12 Data from our study and from the study by Li et al 12 indicate that the antagonism between quinolones and fusidic acid might not arise from constitutional properties.…”
Section: Ertek H Yazgi S Erol Et Al In Vitro Antagonism Between Fusidic Acid and Quinolonessupporting
confidence: 47%
“…Li et al 12 showed unequivocally an antagonistic interaction between ciprofloxacin and all the protein synthesis inhibitors (PSIs) tested by the fractional maximal effect (FME) method, 11 while the same study yielded variable results with either the conventional checkerboard technique or the time-kill method. The FME method demonstrated a similar degree of antagonism against ciprofloxacin by tetracycline, chloramphenicol and erythromycin, and a much lower level of inhibition by tobramycin.…”
Section: Ertek H Yazgi S Erol Et Al In Vitro Antagonism Between mentioning
confidence: 99%